2020
DOI: 10.1063/5.0003312
|View full text |Cite
|
Sign up to set email alerts
|

Large temperature coefficient of resistance in atomically thin two-dimensional semiconductors

Abstract: The temperature coefficient of resistance (TCR) of thin metal lines is often used for applications in thermometry, bolometers, or thermal accelerometers. However, metal TCR is much degraded in nanometer-thin films due to strong surface scattering, preventing their use as fast thermal sensors, which simultaneously require low thermal mass and large TCR. In contrast, here we show that the TCR of doped two-dimensional (2D) semiconductors is large (∼0.3% K−1 at 300 K in MoS2 and MoTe2) even at sub-nanometer thickn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 49 publications
1
20
0
Order By: Relevance
“…First, comparing the effective 1L MoS 2 mobilities (μ eff , squares), we observe that our values (29 and 33 cm 2 V –1 s –1 from 560 °C growths at a reduced 490 Torr pressure) are similar to the μ eff from MoS 2 grown at higher temperatures, up to 850 °C. ,, (Recent simulations have shown that mobilities in this range are limited by point defects, most likely, charge impurities and sulfur vacancies. , ) Field-effect mobility (μ FE ) data reported for 1L MoS 2 grown at 850 °C (lighter hollow triangles) are also included as a box-and-whisker plot (average μ FE of 34.2 cm 2 V –1 s –1 outlined in the black box), in good agreement with the 850 °C effective mobility. For CVD-grown 1L MoS 2 using solid-source precursors, our values are the highest reported mobilities to date with a thermal budget below 2 h at 600 °C.…”
Section: Electrical Results and Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…First, comparing the effective 1L MoS 2 mobilities (μ eff , squares), we observe that our values (29 and 33 cm 2 V –1 s –1 from 560 °C growths at a reduced 490 Torr pressure) are similar to the μ eff from MoS 2 grown at higher temperatures, up to 850 °C. ,, (Recent simulations have shown that mobilities in this range are limited by point defects, most likely, charge impurities and sulfur vacancies. , ) Field-effect mobility (μ FE ) data reported for 1L MoS 2 grown at 850 °C (lighter hollow triangles) are also included as a box-and-whisker plot (average μ FE of 34.2 cm 2 V –1 s –1 outlined in the black box), in good agreement with the 850 °C effective mobility. For CVD-grown 1L MoS 2 using solid-source precursors, our values are the highest reported mobilities to date with a thermal budget below 2 h at 600 °C.…”
Section: Electrical Results and Discussionsupporting
confidence: 61%
“…13,16,[28][29][30] (Recent simulations have shown mobilities in this range are limited by point defects, most likely charge impurities and sulfur vacancies. 69,70 ) Field-effect mobility (µFE) data reported for 1L MoS2 grown at 850°C (lighter hollow triangles) are also included as a box-andwhisker plot (average µFE of 34.2 cm 2 V -1 s -1 outlined in the black box) 16 in good agreement with the 850°C effective mobility. For CVD-grown 1L MoS2 using solid source precursors, our values are the highest reported mobilities to date with a thermal budget below 2-hours at 600°C.…”
Section: Electrical Results and Discussionmentioning
confidence: 78%
“…51,53 This places an upper bound on the defect density in our films, <10 13 cm −2 (interdefect distance < 3.2 nm) even after the metal deposition. A lower bound on the defect density of our asgrown films (before metal deposition) is offered by independent transport simulations, 56,57 which found an impurity density of ∼1.5 × 10 12 cm −2 (average separation ∼8 nm) when all impurities are assumed located in the MoS 2 sheet. (We note that photoluminescence can also be used to analyze defects in bare MoS 2 films, 58,59 but metal-induced nonradiative recombination can obscure this effect in our samples.…”
Section: Resultsmentioning
confidence: 97%
“…Therefore, a positive contribution from the PVE and PCE mechanisms is expected in our devices using the broadband white light source which should overcome the bandgap differences in the two materials. The temperature coefficient of resistance (TCR) at 100 K for BP bolometer is about 0.17 and −0.16% K −1 at 300 K, compared with that of monolayer MoS 2 reported by Khan et al [ 50 ] which is 0.53% K −1 at 100 K and 0.27% K −1 at 30 °K. [ 50 ] Moreover, TCR of −2.9% K −1 was reported for pulsed laser deposited MoS 2 % and 900% K −1 for graphene–based pyroelectric bolometers.…”
Section: Resultsmentioning
confidence: 85%
“…The temperature coefficient of resistance (TCR) at 100 K for BP bolometer is about 0.17 and −0.16% K −1 at 300 K, compared with that of monolayer MoS 2 reported by Khan et al [ 50 ] which is 0.53% K −1 at 100 K and 0.27% K −1 at 30 °K. [ 50 ] Moreover, TCR of −2.9% K −1 was reported for pulsed laser deposited MoS 2 % and 900% K −1 for graphene–based pyroelectric bolometers. [ 51 ]…”
Section: Resultsmentioning
confidence: 85%